TOLERANSI BUI SALAK TERHADAP PENURUNAN KADAR AIR, SUHU DAN SERANGAN JAMUR - PURWANTO, Y.; RAHAYU, R. D.; SUTARNO, HADI (BERITA BIOLOGI, 1988)
Y. PURWANTO, R. D. RAHAYU & HADI SUTARNO.1987. Tolerance of salak seeds on moisture content, temperature and fungal attack.Berita Biologi 3(8): 390 -395.Salak (Salacca edulis var.amboinensis) seeds are difficult to withstand in long term storage.For keeping its viability in storage their tolerance on moisture content,temperatur and fungal attack were studied.Decreasing moistur content influenced salak seed viability. Salak seeds would not afford to sprout.If moisture content reached 24.9%.By moisture content of 47.5%,seed viability dropped to 50.00%.Treatment of storage at temperatures of 10°C, 15 C and 20 C decreased moisture content sjid fungal attack less than at 25°C' and control. Dipping Dithane M45 treatment decreased fungal attack obviously, but it also reduced seed viability.